Changes in psychotropic prescription medication use and their relationship with mortality among people with traumatic spinal cord injury. Issue 7 (July 2018) - Cao, Yue; Clark, Jillian; Krause, James
Abstract Study design Prospective cohort study. Objective To identify the relationship of frequency of prescription medication use to treat pain, spasticity, sleep, and depression/stress, and change in prescription medication use with risk of all-cause mortality. Setting This study was initiated at a specialty hospital in the Southeastern USA, with follow-up and data analysis at an academic medical center in the Southeastern United States. Methods Prospective data were collected in 1997–1998 (Time 1) and 2007–2009 (Time 2), with mortality determined as of 31 December 2014. The initial participant cohort was comprised of 1386 participants with traumatic SCI who were adults and a minimum of 1-year post-injury at enrollment in 1997–1998. Of these, 863 participated at follow-up and 861 were included in the current mortality analysis. Results The frequency of taking prescription medication increased over the 10-year timeframe, particularly for sleep and pain. Each type of prescription medication at Time 1 was associated with later mortality, and an increase in medication use over time was associated with a greater risk of mortality for three of the four conditions (all except spasticity). A decrease in the frequency of pain medication use over time was associated with a decreased risk of all-cause mortality. Conclusions More frequent use of prescription medication to treat pain, sleep, and depression/stress is related to all-cause mortality, and increases in the use of medications to treat these conditions is associated with elevated risk of all-cause mortality.